Gross Negligence Manslaughter in Healthcare: Time for a Restorative Justice Approach?. (27th May 2020) - Farrell, Anne-Maree; Alghrani, Amel; Kazarian, Melinee
Abstract: This article explores the merits of employing a restorative justice approach in cases of gross negligence manslaughter involving healthcare professionals, in line with the recent policy turn towards developing a just culture in addressing episodes of healthcare malpractice within the National Health Service in England. It is argued that redress for victims and rehabilitation of offenders should operate as key values, underpinning the adoption of a restorative justice approach in such cases. It would also be vital that a structured pathway was designed that established suitable protocols and safeguards for both victims and offenders taking account of problematic issues such as the informality of the process, power asymmetries between parties, and the context in which the offence took place. Taking all such matters into account, we propose that consideration be given to establishing a pilot involving the use of restorative justice in cases of gross negligence manslaughter involving healthcare professionals, which would be subject to judicial and stakeholder oversight to ensure transparency and accountability, which in turn could inform future policy options.